Successful outcome in a ruptured heterotopic pregnancy - Jain, Amrita; Kurkal, Nidhi; Aggarwal, Vaishali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A heterotopic pregnancy is a simultaneous intrauterine pregnancy and an ectopic pregnancy. It is a rare condition; however, the increasing use of artificial reproductive techniques is increasing the incidence of heterotopic pregnancy. Most of the patients with heterotopic pregnancy have a previous history of infertility or tubal diseases. Diagnosis of ectopic pregnancy should not be missed out as quite often it is a precious pregnancy and a ruptured ectopic can change the outcome of intrauterine pregnancy as well. A 30-year-old female primigravida with 3 months of gestational age, (in vitro fertilization (IVF) conception) presented to casualty with complaints of bleeding per vaginum since morning. Patient was of gestational age 9 weeks 2 days by a 6 weeks scan at the time of presentation. A Provisional diagnosis of threatened abortion was made, 36 hours later, patient started complaining of acute pain in abdomen. In view of examination findings and ultrasound scan, decision was taken to perform emergency laparotomy. Intra-op findings were consistent with a right ruptured ectopic pregnancy which was missed on previous scans. Histopathology report confirmed findings of right ectopic pregnancy. Heterotopic pregnancy can occur even if the earlier scans are unable to detect the ectopic pregnancy. Patient presenting with symptoms of pain in abdomen and bleeding per vaginum should not be neglected especially in cases of IVF conception. Clinicians should keep in consideration for possibility of heterotopic pregnancy. Early diagnosis and prompt management can increase the survival of intrauterine pregnancy and decrease maternal morbidity and mortality.